Vitamin E supplementation prevents obesogenic diet-induced developmental abnormalities in SR-B1 deficient embryos - Quiroz, Alonso; Belledonne, Gabriela; Saavedra, Fujiko; González, Javier; Busso, Dolores (Frontiers in Cell and Developmental Biology, 2024)
Genetic and environmental factors influence the risk of neural tube defects (NTDs), congenital malformations characterized by abnormal brain and spine formation. Mouse embryos deficient in Scavenger Receptor Class B Type 1 (SR-B1), which is involved in the bidirectional transfer of lipids between lipoproteins and cells, exhibit a high prevalence of exencephaly, preventable by maternal vitamin E supplementation. SR-B1 knock-out (KO) embryos are severely deficient in vitamin E and show elevated reactive oxygen species levels during neurulation. We hypothesized that a high-fat/high-sugar (HFHS) diet consumed by heterozygous SR-B1 female mice would impair maternal vitamin E status and increase the incidence of NTDs in SR-B1 KO embryos from heterozygous intercrosses. HFHS-fed SR-B1 HET females exhibited altered glucose metabolism and excess circulating lipids, along with a higher incidence of embryos with developmental delay and NTDs. Vitamin E supplementation partially mitigated HFHSinduced maternal metabolic abnormalities and completely prevented embryonic 2 malformations, likely through indirect mechanisms involving the reduction of oxidative stress and improved lipid handling by the parietal yolk sac.